Deciphering the mechanisms linking school leadership to instructional practices through collective teacher efficacy: The moderated mediation role of school climate - Alanoglu, Muslim; Uslukaya, Alper; Vural, Gursen; Turan, Cihat; Demirtas, Zulfu (Sage Publications Ltd, 2026)
The present study aims to examine the relationship between school leadership and teachers' instructional practices and to explore the roles of collective teacher efficacy and school climate in this association. Data were collected from 2663 teachers working in 135 schools across 12 regions of T & uuml;rkiye. Structural equation modelling was employed using Bayesian estimation. The findings indicate that school leadership is positively associated with teachers' instructional practices. Furthermore, collective teacher efficacy was found to mediate the relationship between school leadership and instructional practices. Finally, school climate was found to moderate both the direct relationship between school leadership and collective teacher efficacy and the indirect relationship between school leadership and instructional practices through collective teacher efficacy. These results highlight the critical role of school leadership in relation to teachers' instructional practices and suggest that collective teacher efficacy may function as a key psychological mechanism underlying this association. Moreover, a positive school climate appears to be an important contextual factor that can strengthen school leadership on both collective teacher efficacy and instructional practices. Therefore, the study emphasises the need to conceptualise leadership as a context-sensitive and interactional process and offers important theoretical and practical implications for school leadership practices in centralised education systems.
Keywords: Leadership; school leadership; collective teacher efficacy; school climate; instructional practices